PENGEMBANGAN MEDIA KOPER EDUKATIF BERBASIS PERMAINAN TRADISIONAL PADA MATERI SOAL CERITA PENYAJIAN DATA SISWA KELAS V SEKOLAH DASAR - Dwi Saputri, Dela Amelia; Yudi Purwoko, Riawan; Ratnaningsih, Arum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop a Koper Edukatif learning media based on traditional games on the material of data presentation story problems for fifth grade elementary school students and determine its feasibility in terms of validity, practicality, and effectiveness. This research is a Research and Development using the ADDIE model. The subjects of this study were 16 fifth-grade students of SD Negeri Dewi. The research instruments included observation sheets, interview guidelines, media expert validation sheets, material expert validation sheets, practitioner expert validation sheets, student response questionnaires, and post-tests. Data analysis techniques used percentage formulas to determine validity, practicality, and effectiveness. The results showed that the Koper Edukatif learning media was developed through the ADDIE stages of Analysis, Design, Development, Implementation, and Evaluation. The feasibility results showed that the media expert validation obtained 93.68% (very valid), material expert validation obtained 70% (valid), and practitioner validation obtained 81.66% (very valid). The practicality test in the limited trial obtained 70% (practical), and in the extensive trial obtained 92.5% (very practical). The effectiveness test showed a classical completeness percentage of 87.5% (very effective). Thus, the Koper Edukatif learning media based on traditional games is declared feasible to be used in learning mathematics on the material of data presentation story problems for fifth-grade elementary school students.